Avaliando a dimensão biofísica da economia brasileira: uma análise sociometabólica no período 1970-2019 - Araújo, Anderson Henrique dos Santos (2022)
This dissertation investigates the Brazilian economic and biophysical dynamics using a theoretical and methodological framework converging to ecological economics. It means that we recognize there are limits to expanding the economic system. Thus, we have used Socioeconomic Metabolism (MSE) as an analytical category that measures the tangible flows of matter and energy for a given economic system, that is the interactions between the natural world and societies. The central hypothesis is that, from the 1970s onwards, the different phases of Brazil's economic evolution determined its biophysical evolution, in addition to which economic policy choices have relevant impacts on ecological efficiency. We have used theoretical, descriptive, and empirical elements to achieve the proposed objectives, dividing the dissertation into five chapters. The first two chapters conceptualize sociometabolism, list the main converging features between MSE and ecological economics, and map the potential of sociometabolic research (using a bibliometric study). The third chapter explores the relevance of material flow analysis (MFA) as a method, its applicability to the analysis of economicecological phenomena, and the construction of our methodological framework, which supported the following chapters. In the fourth chapter, the emphasis is on Brazil. We describe its economic and biophysical trajectory in the last fifty years, characterized by the expansion of domestic material consumption (DMC), increase in metabolic rate, the increase in material intensity (and emissions), and a greater exchange of material resources to other economies. Finally, we used an econometric frequency domain analysis model in the fifth chapter. It estimated 96 causal relationships between DMC categories and economic and environmental growth variables, indicating that Brazil is an important consumer of iron ore, biomass, and crude oil and that such variables contribute to economic growth while causing an increase in emissions levels. The general results confirm the relevance of sociometabolism and that from 1970 to 2019, there was ecological inefficiency in Brazil, strengthening the need for a sociometabolic transition that emphasizes sustainability.